Becoming a priest: canonical discipline and criteria on suitability for candidates - Szuromi, Szabolcs Anzelm; Álvarez de las Asturias, Nicolás (Aus Religion und Recht, 2019)
Intro -- Contents -- SZABOLCS ANZELM SZUROMI AND NICOLÁS ÁLVAREZ DE LAS ASTURIAS Introduction -- SZABOLCS ANZELM SZUROMI AND NICOLÁS ÁLVAREZ DE LAS ASTURIAS Epilogue: Continuity, Changes, and Transformations -- Bibliography -- Contributors.